Development of Lactic Acid Fermented Beverage Made from The Extract of Brown Rice and Mungbean Mixture - E.Y. Purwani; Narta Narta (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1999)
-